Enhanced Visible Light Absorption by 3C-SiC Nanoparticles Embedded in Si Solar Cells by Plasma-Enhanced Chemical Vapor Deposition. (24th November 2013) - Parida, Bhaskar; Choi, Jaeho; Lim, Gyoungho; Kim, Kiseok; Kim, Keunjoo
Abstract : Solar cells with 3C-SiC nanoparticles embedded in the Si were investigated by plasma-enhanced chemical vapor deposition. Several sizes of SiC nanoparticles were used as the intermediate layer for the solar cell. The Si thin films showed the formation of micro- and nanocrystallites on the SiC nanoparticle sites, which play an important role of heating block as a nanosubstrate. The Raman spectra revealed that the SiC nanoparticles were embedded in mixed phases of amorphous and nanocrystalline Si. Compared to the conventional solar cell sample, the photoreflectance was significantly reduced in the UV/visible spectral region due to the presence of the embedded 3C-SiC nanoparticles. The Si nanocrystals formed by the thin film deposition played an important role in reducing the photoreflectance within the visible to infrared spectral zones. Furthermore, the SiC nanoparticles contributed less in the photoabsorption at a longer infrared spectral zone wavelength of 1200 nm.